The endocannabinoid system in the human granulosa cell line KGN. (5th March 2016) - Ernst, Jana; Grabiec, Urszula; Greither, Thomas; Fischer, Bernd; Dehghani, Faramarz
Abstract: Ovarian steroidogenesis is embedded in a sensitive network of regulatory mechanisms crucial for human fertility. The endocannabinoid system (ECS) represents an intrinsic modulating system involved in the regulation of endocrine functions. In the present study we characterized the ECS in the human granulosa cell line KGN and its impact on gonadotropin sensitivity and steroid hormone synthesis under basal and FSH-stimulated conditions. Expression studies were performed and estradiol was measured. CB1, CB2, DAGL, FAAH, GPR55, MAGL, NAPE-PLD and TRPV1 were expressed without FSH-dependent effects. Treatment with selective cannabinoid receptor agonists reduced basal but not FSH-stimulated estradiol and CYP19 . Progesterone was not altered by ECS manipulation. CB1 agonist changed the expression of miRNAs associated with granulosa cell function, e.g. miR-23a, miR-24, miR-181a and miR-320a. Present data indicate a modulating role of the intrinsic ovarian ECS in the regulation of estradiol synthesis. Highlights: The human granulosa cell line KGN express receptors and enzymes of the ECS. Expression of ECS elements occur in FSH-independent manner. Manipulation of cannabinoid receptors affects estradiol but not progesterone.